Planned Innovation in Improving the Quality of Islamic Education Management - Suprapto, Suprapto; Islah, Islah; Giyoto, Giyoto (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2024)
This study analyzed planned innovation to improve the quality of Islamic education management at SMA MTA Surakarta boarding school. It was conducted using a qualitative approach and a case study method to explore and understand information from taking steps to improve strategies of quality education management. The information was analyzed by (a) processing and preparing information for analysis; (b) reading all the data; (c) describing the setting (domain), people (participants), and categories; (d) presenting descriptions in qualitative narratives/reports; and (e) making interpretations. This study showed that 1) to increase teachers' competency. 2) educational innovations at SMA MTA Surakarta include: a) strengthening boarding school governance b) Strengthening the character of the school community c) Innovation in education management, d) Innovation in increasing the competence of teachers and schools e) Innovation in facilities and infrastructure f) Innovation in developing students' soft skills to provide students with provisions so they can adapt to the demands of developments in science and technology. The forms of activity are very varied. As an Islamic Educational Institution, it should implement strategic management that is systematic, consistent, programmed, comprehensive, and sustainable.